A Story Grows in Rural Uganda: Studying the Effectiveness of the Storytelling/Story-Acting (STSA) Play Intervention on Ugandan Preschoolers' School Readiness Skills. (3rd July 2019) - Goodman, Geoff; Dent, Valeda F.
ABSTRACT: Children in the developing world are at far greater risk for emotional, psychological, and health challenges; at the same time, they have little access to clinical interventions or other support services. The intervention presented in this study is a low-cost, play-based intervention that we believed could help to address early learning and developmental challenges in preschool children in under-resourced areas, in this case, rural Uganda. This study explores the connection among storytelling, story-acting, and school readiness skills, which include emergent literacy, receptive vocabulary, and theory of mind. Ugandan children ages 3 to 5 were randomly assigned to participate in either the Storytelling/Story-Acting (STSA) play intervention ( n = 63) or a story-reading activity ( n = 60) for one hour twice per week for six months. With the aid of translators, all children were assessed for school readiness skills (emergent literacy, receptive vocabulary, and theory of mind) before and after the six-month intervention. Caregivers were also administered an interview that assessed their educational level, quality of life, reading aloud to target child, social support, and total possessions. Overall, participants benefited significantly from a story-reading activity with or without STSA. When examining both groups together ( N = 121 post-intervention), school readiness skills significantly improved. Caregiver variables also predicted these three child outcome variables at baseline, suggesting that caregivers play a significant role in the development of their children's school readiness skills. Implications for these findings are discussed.